An investigation of flow over high roughness - Kawatani, Takeshi, author; Sadeh, Willy Z., author; Colorado State University, publisher (Colorado State University. Libraries, 1971)
An experimental investigation of the atmospheric boundary-layer flow on high roughness was conducted by simulating the flow over a forest canopy in a meteorological wind tunnel. The model forest canopy used consisted of plastic simulated-evergreen trees. The measurements were carried out at constant free-stream velocity and under thermally neutral conditions. Two canopy densities were tested to explore the effects of the roughness density on the flow. One roughness density was half of the other. The results indicate that the mean velocity profiles within the fully developed flow region can be described by generalized logarithmic relationships. For the flow in the inner zone, the free-stream velocity and the roughness height are the similarity parameters for the velocity and the vertical distance, respectively. In the outer zone the freestream velocity and the momentum thickness are the scaling parameters. The roughness density has a strong influence on the momentum loss and the upward flow displacement in the transition region. The shape of the roughness element affects the mean velocity distribution inside the canopy, i.e., jetting effect. The internal boundary-layer thickness was determined based on the turbulent shear-stress distribution. It is found that the flow near the canopy leading edge has two-dimensional wake-like characteristics. The latter are due to the canopy frontal area which is a drastic step obstruction. The existence of an inertial subrange in the fully developed flow region is doubtful although local isotropy occurs for eddies smaller than 2% of the total boundary-layer thickness. The evolution of turbulent energy associated with various size eddies along the canopy can be successfully described by a discretized-energy analysis.
CER71-72TK-WZS3.
August 1971.
Prepared jointly for U.S. Army Electronics Command Contract No. DAAB07-68-C-0423 and Office of Naval Research Contract No. NO014-68-A-0493-0OO1.
Circulating copy deaccessioned 2020.
Keywords: Air flow -- Mathematical models; Meteorology; Atmospheric circulation; Boundary layer